2018
DOI: 10.1140/epja/i2018-12626-y
|View full text |Cite
|
Sign up to set email alerts
|

The enhancement of v4 in nuclear collisions at the highest densities signals a first-order phase transition

Abstract: The beam energy dependence of v 4 (the quadrupole moment of the transverse radial flow) is sensitive to the nuclear equation of state (EoS) in mid-central Au + Au collisions at the energy range of 3 < √ s N N < 30 GeV, which is investigated within the hadronic transport model JAM. Different equations of state, namely, a free hadron gas, a first-order phase transition and a crossover are compared. An enhancement of v 4 at √ s N N ≈ 6 GeV is predicted for an EoS with a first-order phase transition. This enhanced… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
12
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1
1

Relationship

3
5

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 71 publications
(74 reference statements)
4
12
2
Order By: Relevance
“…[20]. Furthermore, it is recently shown that v 4 is also enhanced by the softening [39]. An interesting feature of the enhancement of v 4 is that v 4 is positive for the out-of-plane emission in contrast to the v 2 .…”
Section: Gev)mentioning
confidence: 97%
“…[20]. Furthermore, it is recently shown that v 4 is also enhanced by the softening [39]. An interesting feature of the enhancement of v 4 is that v 4 is positive for the out-of-plane emission in contrast to the v 2 .…”
Section: Gev)mentioning
confidence: 97%
“…Results available at RHIC [63][64][65][66] , over a range of beam energies studied in min-bias Au + Au collisions. In [38], an attempt has been made to study this ratio using JAM model. In Fig 21, we show this ratio as function of beam energy (E Lab ).…”
Section: Energy Dependencementioning
confidence: 99%
“…According to recent hydrodynamical predictions [35], v 4 encodes an important information on the underlying collision dynamics. Recently [38], the beam energy dependence of v 4 was studied using microscopic transport model JAM [17].…”
Section: Introductionmentioning
confidence: 99%
“…Many theoretical and experimental devoted to locate the CP [11,12]. One avenue is to classify the smooth crossover and first order phase transition using the information from the final state particle spectra and collective flow [13][14][15][16][17][18][19][20][21][22][23][24][25]. This method looks for the consequences of the softening of the equation of state since the pressure gradients are much smaller in a medium with a first order phase transition than a crossover phase transition, which leads to slower fluid acceleration and smaller transverse momenta of final state particles.…”
Section: Introductionmentioning
confidence: 99%